Influences of Organic Cation Transporter Polymorphisms on the Population Pharmacokinetics of Metformin in Healthy Subjects - Yoon, Hwa; Cho, Hea-Young; Yoo, Hee-Doo; Kim, Se-Mi; Lee, Yong-Bok (The AAPS journal, 2013)
This study investigated the effects of genetic polymorphisms in organic cation transporter (OCT) genes, such as OCT1-3, OCTN1, MATE1, and MATE2-K, on metformin pharmacokinetics. Of particular interest was the influence of genetic polymorphisms as covariates on the variability in the population pharmacokinetics (PPK) of metformin using nonlinear mixed effects modeling (NONMEM). In a retrospective data analysis, data on subjects from five independent metformin bioequivalence studies that used the same protocol were assembled and compared with 96 healthy control subjects who were administered a single oral 500 mg dose of metformin. Genetic polymorphisms of OCT2-808 G > T and OCTN1-917C > T had a significant ( P < 0.05) effect on metformin pharmacokinetics, yielding a higher peak concentration with a larger area under the serum time–concentration curve. The values obtained were 102 ± 34.5 L/h for apparent oral clearance (CL/ F ), 447 ± 214 L for volume of distribution ( V d / F ), and 3.1 ± 0.9 h for terminal half-life (mean ± SD) by non-compartmental analysis. The NONMEM method gives similar results. The metformin serum levels were obtained by setting the one-compartment model to a first-order absorption and lag time. In the PPK model, the effects of OCT2-808 G > T and OCTN1-917C > T variants on the CL/ F were significant ( P < 0.001 and P < 0.05, respectively). Thus, genetic variants of OCTN1-917C > T, along with OCT2-808 G > T genetic polymorphisms, could be useful in titrating the optimal metformin dose.